2018
DOI: 10.3847/1538-4357/aad4a1
|View full text |Cite
|
Sign up to set email alerts
|

M31 PAndromeda Cepheid Sample Observed in Four HST Bands

Abstract: Using the M31 PAndromeda Cepheid sample and the HST PHAT data we obtain the largest Cepheid sample in M31 with HST data in four bands. For our analysis we consider three samples: A very homogeneous sample of Cepheids based on the PAndromeda data, the mean magnitude corrected PAndromeda sample and a sample complementing the PAndromeda sample with Cepheids from literature. The latter results in the largest catalog with 522 fundamental mode (FM) Cepheids and 102 first overtone (FO) Cepheids with F160W and F110W d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In R16 we included measurements for 375 PHAT Cepheids before the availability of those from Li et al (2021). An expanded compilation from Kodric et al (2018) includes 522 Cepheids from the PHAT program with 3 < P < 78 days. We use the latter sample as an alternative to Li et al (2021) in some variants of our baseline analysis in Section 6.5 because of its powerful leverage to examine evidence of a possible break in the P-L relation near P ≈ 10 days.…”
Section: Cepheids In M31mentioning
confidence: 99%
See 1 more Smart Citation
“…In R16 we included measurements for 375 PHAT Cepheids before the availability of those from Li et al (2021). An expanded compilation from Kodric et al (2018) includes 522 Cepheids from the PHAT program with 3 < P < 78 days. We use the latter sample as an alternative to Li et al (2021) in some variants of our baseline analysis in Section 6.5 because of its powerful leverage to examine evidence of a possible break in the P-L relation near P ≈ 10 days.…”
Section: Cepheids In M31mentioning
confidence: 99%
“…Fits 27 and 28 exchange the Li et al (2021) sample of M31 Cepheids for the PHAT sample from Kodric et al (2018) with a 10 fold increase in the number of variables, but with filters that are transformed to the set of three used elsewhere rather than directly observed with them. The main value of this change is to gain further traction of a possible break at P = 10 days as discussed in the prior section.…”
Section: M31 Variantsmentioning
confidence: 99%
“…Fits 27 and 28 exchange the Li et al (2021) sample of M31 Cepheids for the PHAT sample from Kodric et al (2018) with a ten-fold increase in the number of variables, but with filters that are transformed to the set of three used elsewhere rather than directly observed with them. The main value of this change is to gain further traction of a possible break at P = 10 d as discussed in the prior section.…”
Section: M31 Variantsmentioning
confidence: 99%
“…Kodric et al (2018b) find a broken slope for M31 Cepheids in r, i, g, and Wesenheit bands. However, Riess et al (2016) did not find a broken slope in their m W H relation and Kodric et al (2018a) did not find a broken PLR slope in any of their samples using 522 fundamental mode Cepheids and 102 first overtone Cepheids in F 160W and F 110W as well as 559 fundamental mode Cepheids and 111 first overtone Cepheids in F 814W and F 475W , which is the largest Cepheid sample set compiled to date. To investigate the effect of Cepheids with P < 10 days on our distance determination, we removed Cepheids GRP-11.25609+41.56927 (PAndromeda ID: 1068323, Period = 6.85 days), GRP-11.03915+41.30692 (PAndromeda ID: 104540, Period = 9.362 days), GRP-11.20822+41.44917 (PAndromeda ID: 237868, Period = 4.133 days) and GRP-11.24332+41.50926 (PAndromeda ID: 1052211, Period = 5.751 days) from the gold+silver sample.…”
Section: Nir Distance Determinationmentioning
confidence: 83%
“…Blending has been shown to bias ground-based observations by up to 0.2 mag (Mochejska et al 2000;Vilardell et al 2007), and both crowding and differential extinction cause high dispersion in the Cepheid PLR. While past studies (Macri et al 2001;Riess et al 2012;Wagner-Kaiser et al 2015;Kodric et al 2018a) have shown that space-borne observations can help reduce the effects of crowding and blending, inhomogeneities between the filter systems used to observe Cepheids in M31 and their geometric calibrations yielded uncertainties in the distance measurements between 3% and 5%, limiting our knowledge of the distance to M31 and studies which use M31 to calibrate stellar luminosities.…”
Section: Introductionmentioning
confidence: 99%